High Risks for Fiji Divers in Pacific Documentary 'Disturbing' - Milligan, C (Pacific Media Centre, Creative Industries Research Institute, AUT University, 2016)
This is a report from the Pacific International Documentary Festival 2016, held in Tahiti in January/February 2016. It discusses the festival and focuses on how documentary can draw attention to political issues in the Pacific, centring on the film 'Les Salaires des Profondeurs', a film which shows the lives and suffering of deep-sea divers working in Fiji. http://asiapacificreport.nz/2016/03/06/high-risks-for-fiji-fishermen-in-pacific-documentary-disturbing